(untitled) (Nigerian Journal of Technology, 2018)
Flexibility overtime has been known to enhance the peculiarity of a space, making spaces adaptable to multipurpose use, without altering the functional requirements. The design features and techniques that allow for changing situations in the use and operation of spaces are the focus of this paper. Components such as walls, floors and roofs are the design features that affect space in any building. Event centres being hubs for cultural and social activities, attract an unpredictable population, hence the need for flexible venues for event centres which are fast becoming stable and developing features of any city. The study assessed available event centres and the design features used to achieve flexibility, examining their adaptation to inadequacy of event spaces in selected event centres in Minna Niger state. Observation schedules was used as instrument to obtain data, the data collected was then analysed using Microsoft excel. It was observed from the study that all event centres had adaptability as their flexible design approach and this is as a result of the use of large open spaces, however 80% of event centres in Minna, Niger state failed to have flexible design features. The 20% that provided few of these features used curtain as flexible design elements. The paper recommended that design features for flexibility such as moveable walls, retractable roofs and sitting should be used in event centre designs to achieve an effective flexible design. http://dx.doi.org/10.4314/njt.v37i3.5